The Analysis of the Implementation of Tax Planning to Optimize the Payment of Value Added Tax (VAT) Payable - Septian, Anggi; Hakim, Utsman Abdul; Wahono, Puji; Pahala, Indra (The Future of Education Journal, 2025)
Tax Planning is one of the methods used by taxpayers to minimize taxes in order to gain significant benefits. Every taxpayer registered as a Taxable Entrepreneur (PKP) has an obligation to pay and report Value Added Tax (VAT). In addition to these obligations, taxpayers also have the right to engage in tax planning for the VAT they report, as long as it complies with the Minister of Finance Regulations (PMK) and Government Regulations (PER). Companies such as PT Prima Widodo Makmur, PT Transworld Solution Jakarta Selatan, and PT MM have implemented tax planning or management planning strategies for VAT, with the objective of minimizing tax payments to obtain significant financial advantages. This study uses the Systematic Literature Review technique to examine the strategies employed by these three companies.